Recurrent early Paleozoic rifting in the Northern Gondwana margin: Evidence from correlation of metabasalts across the Saxothuringian Zone of the Bohemian Massif - Crowley, Quentin (My University, 2026)
Geodynamic causes of the Rhenohercynian basin opening and Devonian–early Carboniferous rifting within the Saxothuringian Zone of northern peri-Gondwana and the Variscan basement of the Alps remain unresolved. Interpretations with varying numbers of oceanic tracts formed during Paleozoic fragmentation of Peri-Gondwana exist, heretofore without a comprehensive survey linking Rheic rift-related segments. A review of existing data, combined with new evidence from three separate Rheic/Saxothuringian rift system segments in the Bohemian Massif, informs a new three-stage model of their Paleozoic evolution: (1) Late Cambrian–early Ordovician (~505–470 Ma) rifting accompanying back-arc extension along the northern Gondwana margin, was coeval with Rheic Ocean opening between Avalonia and Saxothuringia. Initial bimodal felsic and mafic OIB-like magmas transitioned through T-MORB to MORB-like basalts, common in NE Saxothuringia. (2) Subordinate Silurian–early Devonian (~430–410 Ma) extension of both Saxothuringian and Teplá-Barrandian basement was possibly linked to closure of Iapetus Ocean and accretion of microcontinental fragments to Laurentia. Proximal to the Münchberg Massif, this manifests as strongly alkaline OIB-type volcanism, whereas more tholeiitic magmas prevail in the adjacent Teplá-Barrandian Unit. (3) Middle-Devonian–early Carboniferous (390–340 Ma) extension produced the most voluminous magmatism, similarly progressing from early bimodal alkaline rhyolite and OIB-type basalts to MORB-like compositions proximal to the Saxothuringian ocean tract. This rift-related volcanism overlaps in chemistry and time with alkaline volcanism of the SE edge of Avalonia, grading into of the Rheic/Rhenohercynian oceanic basalts. Late Devonian/early Carboniferous closure of this ocean is linked to cessation of extension, its shift back to the Gondwana margin and opening of the Paleotethys Ocean.
PUBLISHED
Keywords: Saxothuringian; rifting; Gondwana; Paleozoic volcanism; geochemistry; geochronology; radiogenic isotopes; Smart & Sustainable Planet; GEOCHRONOLOGY; Geochemistry